Effects of Tillage Methods on Penetration Resistance, Bulk Density and Saturated Hydraulic Conductivity in a Clayey Soil Conditions - İsmail Celik (Journal of Agricultural Sciences)
Effects of six tillage practices on saturated hydraulic conductivity (HC), soil bulk density (BD), and penetration resistance (PR) were evaluated for a clayey soil (Typic Haploxererts) under semi-arid Mediterranean conditions in a three year study (2006-2009). The experiment was conducted on a randomized complete block design with three replicates. Treatments were: conventional tillage with residue incorporated (CTS), conventional tillage with residue burned (CTB), reduced tillage with heavy tandem disc harrow (RTD), reduced tillage with rotary tiller (RTR), reduced tillage with heavy tandem disc harrow for the first crop + no-tillage for the second crop (RNT), and no tillage (NT). The study was conducted in wheat-corn, wheat-soybean and wheat crop rotations. The tillage effects on HC, BD and PR were significant at soil depth of 0-30 cm. The hydraulic conductivity was higher in CTS, and followed by CTB, RTR, RTD, RNT and NT practices, respectively. The hydraulic conductivity values under NT in 2007 and 2008 were 20% and 30% lower at 0-30 cm depth compared with CTS, respectively. The conventional tillage treatments in the semi-arid conditions improved the HC with decreasing BD and PR of the clayey soil. The BD and PR values were higher under NT treatments than the tilled plots and increased with depth. The values of soil compaction indicators were significantly greater under no-tillage and reduced tillage as compared to those under conventional tillage in all soil depths studied.